Instrumental Variable Estimation of the Causal Effect of Hunger Early in Life on Health Later in Life - Gerard J. van den Berg; Pia R. Pinger; Johannes Schoch (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
We estimate average causal effects of early-life hunger on late-life health by applying instrumental variable estimation, using data with self-reported periods of hunger earlier in life, with famines as instruments. The data contain samples from European countries and include birth cohorts exposed to various famines in the 20th century. We use two-sample IV estimation to deal with imperfect recollection of conditions at very early stages of life. The estimated average causal effects may exceed famine effects by at least a factor three.
Keywords: I12; J11; C21; C26; 330; nutrition; famine; ageing; developmental origins; height; two-sample IV